Chemical and chromatic effects of fermentation temperature on three clones of Pinot noir over two consecutive vintages - Reynolds, Joshua C.; Meusel, R. Cole; Catania, Anibal Alejandro; Casassa, Luis Federico (American Society for Enology and Viticulture (ASEV), 2023)
Three different Pinot noir clones (115, 777, and 828) from the Central Coast of California were subjected to different maceration temperature regimes for 14 days using triplicate fermentations (Cold: 10°C; Hot: 25°C; and Variable: 10°C on days 0 to 7 and 25°C on days 8 to 14) to determine the effect of maceration temperature on color and phenolic extraction across all three clones over two consecutive vintages (2019 and 2020). In 2019, the Hot treatment and the hot portion of the Variable treatment were obtained by exposing the fermentors to direct sunlight, while in 2020, this was achieved by artificial heating. Spectrophotometric analyses showed that at time of pressing, extraction of total phenolics for Cold, Variable, and Hot temperature treatments was 723, 894, and 1031 mg/L, respectively. Similar trends were observed in Cold, Variable, and Hot treatments for anthocyanins (208, 265, and 284 mg/L, respectively), tannins (68, 81, and 123 mg/L, respectively), and polymeric pigments (0.40, 0.46, and 0.51 absorbance units [AU], respectively). Similarly, the average monomeric anthocyanin concentrations of both vintages’ Cold, Variable, and Hot treatments analyzed via high-performance liquid chromatography were 210, 269, and 267 mg/L, respectively; that of flavonols were 26, 28, and 30 mg/L, respectively. Color analysis showed a negative correlation with temperature for CIELab lightness values across Cold, Variable, and Hot treatments (86.69, 84.89, and 83.37, respectively), and positive correlation for red hues (16.05, 17.73, and 20.50, respectively) and wine color (AU 420 + 520 + 620 nm; 0.48, 0.54, and 0.60, respectively). Finally, differences in heating method between the two vintages (direct sunlight in 2019 and a temperature-controlled room in 2020) was a major factor in phenolic extraction.